A BRIEF EXPLORATION OF THE ISLAMIZABLE YORUBA ART AND CULTURE - AL-SHAFI’I, MOHAMMED MUNEER’DEEN OLODO; ABDULLAHI, AUWAL; AL-SHAFI’I, KAFAYAT OMOWUMI OLODO (Innovare Journal of Social Sciences, 2023)
Art and culture it is believed cannot be simply defined. This is based on the complexity of the notions and connotations they both imbibe. A similar difficulty it is faced when determining what is religious, particularly Islamic, in art and culture and what is not. Bearing in mind the complexity of both the definition and the conception, this paper attempts a general definition than can be considered by all sundry and attempts to draw closer some conceptual usages that would not be alleged as taking one beyond the boundary of religion. Islam is both an inclusive and exclusive way of life, and as such is expected to be tolerant in most cases. Art and culture derived from natural instincts would not in any way and form go against Islamic injunctions, if properly dissected and appropriately elucidated. There are many aspects of Yoruba art and culture that are still maintained both during and post adventure of Islam among the Yoruba community. Moreover, Islam has been silent on some others, not giving consent not disproving, due to lack of a direct prohibition from the Shariah law and the Muslim scholars. Art and culture cannot be strictly placed under the category of haram (prohibited acts), and it is the position of this paper that whether we like it or we like it not art and culture are both part of us and so shall we manage them with our ways of life (religion). The paper likes to conclude that the misplacement of the artistic and cultural concepts stem from the misappropriation and misrepresentation of what art and culture are and what they are not. Art and culture are just what they are, and are not what they are not, a water-concept of life that is seldom felt but hard to jettison.